Influence of the deposition interruption on the texture degree of barium hexaferrite BaFe12O19 films. (October 2021) - Kostishin, V.G.; Mironovich, A.Yu.; Timofeev, A.V.; Isaev, I.M.; Shakirzyanov, R.I.; Skorlupin, G.A.; Ril, A.I.
Abstract: BaFe12 O19 films on Al2 O3 (001) substrates were synthesized by ion beam deposition with post-annealing. Three deposition regimes were applied, resulting in unique surface morphology and X-ray diffraction patterns of obtained samples. In the first case, the deposition process was interrupted several times and the sample was subjected to ex situ annealing at 900 °C after each interruption. As a result, a film with high texture degree (about 97 %) was obtained. In the second case, the deposition process was interrupted the same number of times, but during each pause the film remained in the vacuum chamber for 10 min at 300 °C. This approach resulted in a medium texture degree of the sample (about 72 %). In the third case, there were no breaks in the deposition process and the texture of the resulting film was extremely poor. An explanation for the observed differences is proposed. To improve the texture of the films, a second annealing at 1280 °C for 10 h was applied, but as a result strong interdiffusion and misorientation of the grains occurred. Highlights: Interruptions of the deposition of BaFe12 O19 led to an improvement in films texture. Annealing at 1280 °C led to noticeable interdiffusion between BaFe12 O19 and Al2 O3 . Highly textured films were obtained by repeated deposition and annealing technique.